Baroreflex and chemoreflex interaction in high-altitude exposure: possible role on exercise performance - Alvarez-Araos, P.; Jiménez, S.; Salazar-Ardiles, C.; Núñez-Espinosa, C.; Paez, V.; Rodriguez-Fernandez, M.; Raberin, A.; Millet, G. P.; Iturriaga, R.; Andrade, D. C. (Frontiers in Physiology, 2024)
The hypoxic chemoreflex and the arterial baroreflex are implicated in the ventilatory response to exercise. It is well known that long-term exercise training increases parasympathetic and decreases sympathetic tone, both processes influenced by the arterial baroreflex and hypoxic chemoreflex function. Hypobaric hypoxia (i.e., high altitude [HA]) markedly reduces exercise capacity associated with autonomic reflexes. Indeed, a reduced exercise capacity has been found, paralleled by a baroreflex-related parasympathetic withdrawal and a pronounced chemoreflex potentiation. Additionally, it is well known that the baroreflex and chemoreflex interact, and during activation by hypoxia, the chemoreflex is predominant over the baroreflex. Thus, the baroreflex function impairment may likely facilitate the exercise deterioration through the reduction of parasympathetic tone following acute HA exposure, secondary to the chemoreflex activation. Therefore, the main goal of this review is to describe the main physiological mechanisms controlling baro- and chemoreflex function and their role in exercise capacity during HA exposure.